Matrix Approach to Forming a Strategy for the Development of Industrial Enterprises - Abdullaeva Matluba Nematovna (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
Strategic planning is an integral part of the organization’s functioning system. Successful development of the enterprise is impossible, and effective strategic planning is also impossible without matrix tools. The matrix method used in strategic planning allows you to visually present the information being studied, as well as determine the correct line of behavior in a particular situation. Matrix tools, for developing an enterprise development strategy is a set of economic forecasting tools that allow to fully implementing the enterprise strategy in a market economy.